Cost-effectiveness targeting under multiple conservation goals and equity considerations in the Andes - Narloch, U.; Pascal, U.; Drucker, Adam G. (Cambridge University Press, 2011)
Internationally, there is political impetus towards providing incentive mechanisms, such as payments for ecosystem services (PES), that motivate land users to conserve that which benefits wider society by creating an exchange value for conservation services. PES may incorporate a number of conservation goals other than just maximizing the area under a certain land use, so as to optimize multiple benefits from environmental conservation. Environmental additionality (conservation services generated relative to no intervention) and social equity aspects (here an equitable distribution of conservation funds) of PES depend on the conservation goals underlying the cost-effective targeting of conservation payments, which remains to be adequately explored in the PES literature. This paper attempts to evaluate whether multiple conservation goals can be optimized, in addition to social equity, when paying for the on-farm conservation of neglected crop varieties (landraces), so as to generate agrobiodiversity conservation services. Case studies based on a conservation auction in the Bolivian and Peruvian Andes (through which community-based groups identified the conservation area and the number of farmers taking part in conservation, as well as the payment required), identified significant cost-effectiveness tradeoffs between alternative agrobiodiversity conservation goals. There appears to be a non-complementary relationship between maximizing conservation area under specific landraces (a proxy for genetic diversity maintenance) and the number of farmers conserving such landraces (a proxy for agricultural knowledge and cultural traditions maintenance). Neither of the two are closely connected with maximizing the number of targeted farming communities (a proxy for informal seed exchange networks and hence geneflow maintenance). Optimizing cost-effectiveness with regard to conservation area or number of farmers would also be associated with a highly unequal distribution of payments. Multi-criteria targeting approaches can reach compromise solutions, but frameworks for these are still to be established and scientifically informed about the underlying link between alternative conservation goals and conservation service provision.